Changes in Occupational Patterns and Its impact on Health Seeking Behaviour of Denotified Tribal Women - Rao Ambati, Nageswara; Anand, Saurabh (International Journal of Psychosocial Rehabilitation, 2020)
India is always known for its diverse culture and unity in diversity. It is characterised by plurality in religions, castes, sub-castes, races, and diverse societies and cultures. People belonging to such diverse groups represent differences in cultures and practices. In this diversified society, there are many communities that are living in inhuman conditions. Such communities, which include tribals, are not only neglected but are even not considered citizens of this country. They are settled in many regions of the world, and the majority of them are the poorest of the poor. According to the 2011 Census, the population of tribes in the country constitutes 8.06 percent of the total population, while their habitats form 20% of the total geographical landmass of the country. In spite of the protection given to the tribal population by the Constitution of India, tribal’s still remain the most backward ethnic group in India. Their living conditions are generally very dismal on the three most important indicators of development: health, education, and income. Tribes have their own social and cultural practices to treat different kinds of illnesses. These communities possess unique knowledge about health practices and stay away from modern/English medicine. In order to examine the health-seeking behaviour of denitrified tribal women, the researchers used the quantitative method and collected data from 200 respondents with the help of the survey method. The findings of the study highlighted two points: firstly, is there any change in the socio-economic status of women in de-notified tribal communities? If yes, what is its impact on health-seeking behaviour among these communities?. The findings of the study suggest that it is very difficult to address the health care problems of these communities without improving their socio-economic conditions.